Conceptual Model of Architecture of 4-Layer Smart System for Emergency Response system of Negative Interaction of Human to Elephant - sukoco, Agus; Prihatmanto, Ary Setijadi; Yusuf, Rahadian; Arief, Harnios; Putro, Haryanto R (International Journal of Applied Research and Sustainable Sciences, 2024)
The interaction between elephants and humans in the era of smart systems requires a new approach to managing frequent conflicts. In this context, the development of an emergency response system based on smart system technology is very important, both for local communities and national park managers. This system is expected to utilize technology to improve the effectiveness of handling elephant emergencies. This study emphasizes the need to develop an emergency response system based on smart systems to improve the effectiveness of managing elephant-human interactions. Sustainable and participatory system development will be key to creating better solutions to these conflicts in the future.